Robust finite-time almost passivity and practical finite-time stability of uncertain switched nonlinear systems - Xuelian Gao; Hongbo Pang; Chensong Li (Franklin Open, 2025)
In this paper, the robust finite-time almost passivity and practical finite-time stability of a class of switched nonlinear systems with the structural uncertainties are investigated. First, multiple storage functions are adopted to characterize robust finite-time almost passivity property of uncertain switched nonlinear systems, which only requires each subsystem to be passive outside a ball on its active interval. Then, based on the proposed almost passivity concept, practical finite-time stability is obtained. Second, a switching law dependent on states is adopted to make the system robust finite-time almost passive. Third, robust finite-time almost passification is achieved by designing a switching law dependent on the states and a set of robust controllers. The advantage of the designed switching law is that the adjacent storage functions are allowed to increase at each switching point. Finally, an example is provided to verify the validity of the results.